m-2(m-5)=-10m-(2-3m)

Simple and best practice solution for m-2(m-5)=-10m-(2-3m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-2(m-5)=-10m-(2-3m) equation:


Simplifying
m + -2(m + -5) = -10m + -1(2 + -3m)

Reorder the terms:
m + -2(-5 + m) = -10m + -1(2 + -3m)
m + (-5 * -2 + m * -2) = -10m + -1(2 + -3m)
m + (10 + -2m) = -10m + -1(2 + -3m)

Reorder the terms:
10 + m + -2m = -10m + -1(2 + -3m)

Combine like terms: m + -2m = -1m
10 + -1m = -10m + -1(2 + -3m)
10 + -1m = -10m + (2 * -1 + -3m * -1)
10 + -1m = -10m + (-2 + 3m)

Reorder the terms:
10 + -1m = -2 + -10m + 3m

Combine like terms: -10m + 3m = -7m
10 + -1m = -2 + -7m

Solving
10 + -1m = -2 + -7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7m' to each side of the equation.
10 + -1m + 7m = -2 + -7m + 7m

Combine like terms: -1m + 7m = 6m
10 + 6m = -2 + -7m + 7m

Combine like terms: -7m + 7m = 0
10 + 6m = -2 + 0
10 + 6m = -2

Add '-10' to each side of the equation.
10 + -10 + 6m = -2 + -10

Combine like terms: 10 + -10 = 0
0 + 6m = -2 + -10
6m = -2 + -10

Combine like terms: -2 + -10 = -12
6m = -12

Divide each side by '6'.
m = -2

Simplifying
m = -2

See similar equations:

| 4x^3-6x^2+2x-3=0 | | -8/9y=8 | | 11x+13=17x+1 | | 9x^3+4x-8x^3-5x= | | 11x^2-3(-8x)= | | 4z/2z^2 | | 3x(5x+1)-2(5x+1)= | | (m-5)9-m=5+3(5m+2) | | 960=p+0.12*2 | | -22z=11v | | X^6-3x^4-2x^2-1=0 | | 5(m-8)+3(4-m)=-32 | | 0.12*2p=960 | | 5x-8x+3=x-3+6 | | 8p+5q-3(3p-7q)= | | 8x^6-125y^6=0 | | 5x-8x+3=c-3+6 | | u+(-5)=10 | | -8v+6(v+5)=18 | | (1/8)m^3-8n^3=0 | | 8x=8+7x | | 5(x-3)=3(x-4) | | 4*16+8-0/5 | | 300-60+x/2=6x | | 5x^2+6x^2= | | -3x+16=-5 | | y=4x^2-16x | | 10(30)-60+x/2=6x | | 5(p-2)+3(p+1)=25 | | 5-2*(3-6x)=10x | | 4=0.0025p | | -6/7-3/7=4/3u+1/3u |

Equations solver categories